2014
DOI: 10.1093/deafed/enu017
|View full text |Cite
|
Sign up to set email alerts
|

Children Who Are Deaf or Hard of Hearing in Inclusive Educational Settings: A Literature Review on Interactions With Peers

Abstract: This review is conducted to describe how children who are deaf or hard of hearing (D/HH) interact with hearing peers in inclusive settings, illustrate the difficulties and challenges faced by them in interacting with peers, and identify effective interventions that promote their social interaction in inclusive education. A systematic search of databases and journals identified 21 papers that met the inclusion criteria. Two broad themes emerged from an analysis of the literatures, which included processes and o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
56
0
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(62 citation statements)
references
References 32 publications
1
56
0
5
Order By: Relevance
“…In Korea, students requiring special education are usually placed in mainstream schools rather than in separate special schools and special classes. Previous studies have emphasized the following principal benefits of inclusive education of implanted children: naturalistic access to typical linguistic and behavioral models of hearing peers, and social acceptance by hearing peers [6,23,24]. Children with CIs in mainstream schools reported having friends with mostly normal hearing (Q1 in Table 3).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Korea, students requiring special education are usually placed in mainstream schools rather than in separate special schools and special classes. Previous studies have emphasized the following principal benefits of inclusive education of implanted children: naturalistic access to typical linguistic and behavioral models of hearing peers, and social acceptance by hearing peers [6,23,24]. Children with CIs in mainstream schools reported having friends with mostly normal hearing (Q1 in Table 3).…”
Section: Discussionmentioning
confidence: 99%
“…Over the past two to three decades, there has been a significant trend towards placing students with special educational needs in mainstream schools rather than in segregated spe-cial schools and special classes [6]. Besides, the proportion of children with CIs in mainstream schools has been steadily increasing [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…The majority of d/Dhh students encounter communication difficulties in the inclusive education classroom [66]. For students who have a profound hearing loss, communication and interaction with hearing students is more challenging than it is for students with mild to moderate or severe hearing loss because the former group often relies on a signed language for communication whereas hard of hearing students often use spoken language [5].…”
Section: Inclusion and The Development Of Language And Literacy Skillsmentioning
confidence: 99%
“…For example, research into the education of deaf/hard of hearing learners in Northern Ireland and Sweden has shown that these children struggle in oral‐based education systems, and in this instance, the best environment appropriate to their needs is a special class or special school (Doherty, ). However, inclusionists assert that there are benefits of inclusive education for this population, including social interaction and contact with peers with normal hearing, social acceptance by hearing peers, and access to typical behavioural and linguistic models of hearing (Eriks‐Brophy et al, ; Xie et al, ). Nonetheless, it has been found that integrating children who are deaf/hard of hearing into mainstream classrooms has not necessarily facilitated acceptance by peers, aided meaningful social interaction, or given deaf/hard of hearing students a sense of inclusion (Bobzien et al, ; Weisel et al, ; Xie et al, ).…”
Section: Inclusion and The Rights Of The Childmentioning
confidence: 99%
“…However, inclusionists assert that there are benefits of inclusive education for this population, including social interaction and contact with peers with normal hearing, social acceptance by hearing peers, and access to typical behavioural and linguistic models of hearing (Eriks‐Brophy et al, ; Xie et al, ). Nonetheless, it has been found that integrating children who are deaf/hard of hearing into mainstream classrooms has not necessarily facilitated acceptance by peers, aided meaningful social interaction, or given deaf/hard of hearing students a sense of inclusion (Bobzien et al, ; Weisel et al, ; Xie et al, ). This has led to some writers arguing that full inclusion in mainstream settings cannot be achieved for deaf learners, due to their specific difficulties with communication and comprehension (Peters, ).…”
Section: Inclusion and The Rights Of The Childmentioning
confidence: 99%